The Dynamics of Public Trust and Social Construction of the Pekanbaru City Fire and Rescue Service - Anas, Shohibul; Hidir, Achmad; Asriwandari, Hesti (Journal of Authentic Research, 2026)
This study examines the dynamics of public trust and the social construction of the Pekanbaru City Fire and Rescue Service in responding to both fire and non-fire emergencies in urban society. Using a qualitative case study design, data were collected through in-depth interviews with the head of the agency and key informants within the organizational structure, supported by field observations and document analysis. The findings reveal that public trust in the Fire and Rescue Service is shaped through a long dialectical process between citizens’ expectations for rapid emergency response and their perception of the slower responsiveness of other public institutions. Through the processes of externalization, objectification, and internalization, reinforced by daily interactions and social media narratives, the community has constructed the Fire and Rescue Service as a responsive, reliable, and multi-functional institution that is always ready to help. This social construction has expanded the institution’s public role beyond its formal mandate and positioned it as a frontline service in addressing various urban problems. The study concludes that this positive public trust should be understood not merely as an institutional image, but as a sociological reflection of changing urban service expectations. These findings contribute to the study of public trust and social construction in urban public services and provide a reflective basis for strengthening inter-agency responsiveness and service governance.